Penggunaan Media Berbasis Augmented Reality (Ar) Melalui Layanan Bimbingan Kelompok Untuk Meningkatkan Motivasi Belajar Siswa Sma Negeri 5 Banda Aceh - Dini Ramadhani; Muslima Muslima (Journal of Innovative and Creativity, 2025)
This study examines the use of Augmented Reality (AR) based media in group guidance services to improve the learning motivation for eleventh-grade students at SMA Negeri 5 Banda Aceh. Using a one-group pretest–posttest design (n-80), a sample of eight students participated in four guidance service sessions utilizing interactive AR materials. The instrument was a validated learning motivation questionnaire (21 of 24 items were valid) and demonstrated high reliability (Cronbach's α = 0.854). Analysis included a normality test, paired sample t-test, and N-Gain calculation. The results showed a significant increase in motivation scores (mean difference = 24.125; t = −17.145; p < 0.001) and an average N-Gain = 0.91 (high category), indicating substantial changes after the intervention. Based on the result, H0 (no effect of AR on learning motivation) was rejected and Ha (there was an effect of AR on learning motivation) was accepted. The discussion highlights the mechanisms of increased motivation through increased attention, material relevance, group interaction, and increased self-efficacy due to the use of AR. Limitations such as the design without a control group, small sample size, and limited intervention duration are discussed as recommendations for further research.